2020
DOI: 10.1088/1742-6596/1511/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of readiness in IT adoption among SMEs manufacturing industry in Jakarta

Abstract: The development of SMEs, especially those based on the manufacturing industry, is highly developed along with the significant market demand. The increasingly important information technology in SMEs will have an impact on increasing productivity, marketing, and efficiency. In this research, measurement of readiness level in the adoption of information technology (IT) will be carried out used to explore the level IT application readiness and to examine factors which influences its application along with the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
1
0
6
Order By: Relevance
“…The outcome is the predicted Actual Acceptance (AS). Previous research has found that developing an information technology adoption plan for SMEs has positive results, with a 76 percent success rate [15][16][17], and that it provides a better understanding of how important technology is now in the corporate world operating a company so that it has the greatest effect on the company's progress [18]. The likelihood that an assets will expand horizontally.…”
Section: Methodsmentioning
confidence: 99%
“…The outcome is the predicted Actual Acceptance (AS). Previous research has found that developing an information technology adoption plan for SMEs has positive results, with a 76 percent success rate [15][16][17], and that it provides a better understanding of how important technology is now in the corporate world operating a company so that it has the greatest effect on the company's progress [18]. The likelihood that an assets will expand horizontally.…”
Section: Methodsmentioning
confidence: 99%
“…Keberadaan bisnis waralaba tidak lepas dari pemenuhan kebutuhan ekonomi pemilik usaha dan peningkatan taraf hidup. Pola pikir para pelaku bisnis selalu menguntungkan selama bisnis bisa berjalan dan sangat mengandalkan naluri bisnis dalam menjalankan bisnis (Sani, Rahman, Budiyantara, & Doharma, 2020). Menurut Suryana (2006:62), pelaku bisnis yang menggunakan konsep kewirausahaan ditentukan oleh faktor motif untuk berprestasi, optimisme, status dan sikap nilai kewirausahaan atau keberhasilan yang dipengaruhi oleh lingkungan internal dan eksternal (Riwayati & Gunadi, 2015).…”
Section: Pendahuluanunclassified
“…Pada tahapan ketiga yaitu Modelling Quick Design dalam tahapan ini Tahap ini membagi 3 pemodelan perancangan yaitu, perancangan perangkat keras, perancangan perangkat lunak dan perancangan sistem secara keseluruhan. Berikut masing-masing model perancangannya (Sani et al, 2020). Kemudian tahapan selanjutnya adalah pengujian dilakukan beberapa pengujian salah satunya yaitu pengujian dilakukan dengan membuka pintu tanpa otentikasi melalui RFID ataupun website, namun dengan cara dibuka secara paksa yang kemudian berhasil hingga pintunya terbuka pada sisi sebelah kiri (kotak berwarna jingga) menunjukkan data terakhir sebelum dilakukan pengujian.…”
Section: Hasil Dan Pembahasanunclassified